Crocetin, a Carotenoid from Gardenia jasminoides Ellis, Protects against Hypertension and Cerebral Thrombogenesis in Stroke‐prone Spontaneously Hypertensive Rats. (18th February 2014) - Higashino, Saori; Sasaki, Yasuto; Giddings, John C.; Hyodo, Kanae; Fujimoto Sakata, Shigeko; Matsuda, Koichi; Horikawa, Yoko; Yamamoto, Junichiro
ABSTRACT Crocetin is a natural carotenoid dicarboxylic acid that is found in the fruit of Gardenia jasminoides Ellis (Cape Jasmine) and in the stamen and pistil of Crocus sativus L. (saffron). It is used worldwide as an important spice, food colorant, and herbal medicine. In the current investigation, we have examined the cardiovascular effects of crocetin using stroke‐prone spontaneously hypertensive rats (SHRSPs). Male SHRSPs (6 weeks old) were classified into three groups: a control group and two crocetin groups (25 and 50 mg/kg/day). The animals were given crocetin for 3 weeks. Body weights in each group were not significantly different during the treatment period, but the increase in systolic blood pressures observed with age was significantly moderated by crocetin. Thrombogenesis, assessed using a He‐Ne laser technique in pial vessels, was significantly decreased. Antioxidant activity, assessed by measuring urinary 8‐hydroxy‐2′‐deoxyguanosine levels, together with urinary nitric oxide (NO) metabolite levels, was increased significantly after treatment. Acetylcholine‐induced vasodilation was measured using the aorta and indicated that endothelial function was significantly improved by crocetin. These results strongly suggest that the antihypertensive and antithrombotic effects of crocetin were related to an increase in bioavailable NO, possibly mediated by decreased inactivation of NO by reactive oxygen species. Copyright © 2014 John Wiley & Sons, Ltd.